2002
DOI: 10.1002/tox.10055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal exposure to volatile organic compounds on the cytokine secretion profile of neonatal T cells

Abstract: Indoor VOC (volatile organic compound) exposure has been shown to be correlated with airway symptoms and allergic manifestations in children. An investigation was conducted within an ongoing birth cohort study (LISA: Lifestyle-Immune System-Allergy) of the association between maternal exposure to VOCs and immune status at birth, in particular the cytokine secretion profile of cord-blood T cells. In a randomly selected group of 85 neonates, cytokine-producing cord-blood T cells were analyzed using intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 33 publications
3
97
1
4
Order By: Relevance
“…If the relationship is cause-and-effect, it is likely that an immune response is part of the mechanism [32]. One study reported that an increased level of IL-4 cytokine production in newborns was associated with maternal exposure to VOCs during pregnancy [33], noting that IL-4 was usually increased in atopic children.…”
Section: Resultsmentioning
confidence: 99%
“…If the relationship is cause-and-effect, it is likely that an immune response is part of the mechanism [32]. One study reported that an increased level of IL-4 cytokine production in newborns was associated with maternal exposure to VOCs during pregnancy [33], noting that IL-4 was usually increased in atopic children.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed by a survey using personal assessment of VOC exposure [134], showing an increased risk of doctor-diagnosed asthma among those exposed to VOCs and, in particular, to aromatic compounds (OR 1.63, 95% CI 1.17-2.27). While two studies suggest that exposure to VOC in utero could have an impact on immune status of newborns [135,136], no epidemiological study using objective measurements reports significant associations between exposure to formaldehyde and allergic sensitisation.…”
Section: Formaldehyde and Vocsmentioning
confidence: 99%
“…This has led to recognition of cytokine expression and secretion as a useful biomarker to assess the status and progression of a host immune response. Since then, numerous studies have used immune markers that include cytokine profiles to evaluate the effect of environmental toxicants such as volatile organic compounds, PCBs, and organochlorines on the immunity of children (Lehmann et al, 2002;Bilrha et al, 2003;ten Tusscher et al, 2003).…”
mentioning
confidence: 99%